Avaliação multicritério para determinar os riscos operacionais mais relevantes em uma instituição financeira cooperativa de crédito - Lima, Emelly Anne Silva de (2023)
The evolution of the financial market over the years has made risk management increasingly important for financial institutions. Operational risk, in particular, is associated with losses existing in all stages of the operation. In this scenario, the management of this risk aims to minimize losses and contribute to the stability of the economy. Although the notoriety of operational risks has been noticed by experts and researchers, there are still gaps regarding the analysis of the degree of importance attributed by financial institutions' managers. Thus, the objective of this research is to determine the most relevant operational risks existing in a financial institution. To achieve the proposed objective, a mixed approach (qualitative and quantitative) was adopted, which begins with a theoretical conceptual framework, followed by an empirical study. In this research, a Systematic Literature Review was carried out and a case study was applied to a credit union financial institution. According to the results of the literature review, the following stand out: the concern with decreasing the minimum capital recommended by the Basel II Capital Accord, the chain reaction to operational risk, and the great importance given to damage to reputation. As for the results obtained in the empirical study, the occurrences of 4 (four) types and 19 (nineteen) operational risk factors were identified. To rank and calculate the degree of importance attributed by the respondents, a multicriteria decision support tool, the Analytic Hierarchy Process (AHP), was used, showing that the highest degrees of importance are related to people management, government policies, physical security of the agencies, and cybersecurity. In addition, it was found the need to align the strategy of the cooperative studied as to the management of operational risks considered as priorities for each manager, in order to assertiveness in mitigation plans.